1998
DOI: 10.1136/jcp.51.2.127
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of invasion frequencies of cultured HEp-2 cells by clinical isolates of Helicobacter pylori using an acridine orange assay.

Abstract: Aims-Recent studies suggest that Helicobacter pylori is an invasive enteropathogen. However, the eYciency with which this pathogen invades mammalian cells remains unknown. Therefore, this study was designed to investigate the invasion frequencies of HEp-2 cells by clinical strains of H pylori. Methods-An acridine orange assay and cultured HEp-2 cell monolayers were used to determine the HEp-2 cell penetration frequencies of 17 clinical isolates and one American Type Culture Collection (ATCC) strain of H pylori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
41
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 21 publications
2
41
0
Order By: Relevance
“…For a very long time, H. pylori was considered an extracellular pathogen (52,53,56), but an increasing number of re- ports based on biospy examination and in vitro infection experiments have indicated that at least some host-associated H. pylori bacteria are located within host epithelial cells (19,28,31,50,62,64,73,79,85). In the present study, we used AGS cells as an infection model in order to demonstrate that the penetration of gastric epithelial cells is a multifactorial process resulting from an intricate interplay between H. pylori and host cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For a very long time, H. pylori was considered an extracellular pathogen (52,53,56), but an increasing number of re- ports based on biospy examination and in vitro infection experiments have indicated that at least some host-associated H. pylori bacteria are located within host epithelial cells (19,28,31,50,62,64,73,79,85). In the present study, we used AGS cells as an infection model in order to demonstrate that the penetration of gastric epithelial cells is a multifactorial process resulting from an intricate interplay between H. pylori and host cells.…”
Section: Discussionmentioning
confidence: 99%
“…Early reports indicated that H. pylori was not present in the gastric mucosa but was present in the mucus layer overlying the gastric tissue (52,53,56). However, in recent years, a number of biospy studies (28,30,62) and cell culture infection models (19,31,50,64,73,79,85) have provided increasing evidence for the intracellular localization of H. pylori. Clearance of intracellular H. pylori has been demonstrated in vitro by using antibiotics with known intracellular activity (40).…”
mentioning
confidence: 99%
“…Although about 10% of H. pylori can adhere to gastric epithelial cells, organisms are rarely found intracellularly (31)(32)(33). Adherence of H. pylori to the gastric epithelium is a complicated process that involves a number of bacterial cell-surface receptors, including the Lewis B-bind- ing (Le b -binding) adhesin BabA (34), an outer membrane protein encoded by babA2 that binds the histo-blood group antigen Le b on the surface of epithelial cells.…”
Section: Role Of Bacterial Virulence Factors In H Pylori Persistencementioning
confidence: 99%
“…HEp-2 cells from a patent with human larynx carcinoma were obtained from the American Type Culture Collection (ATCC CCL 23) and were grown on tissue culture plasticware in basal Eagle's medium supplemented with Hanks' salts, 50 mM L-glutamine, 0.075% sodium bicarbonate, and 15% fetal bovine serum (FBS; Sigma Chemical Co., S. Louis, Mo.). The cells were incubated at 37°C in 5% CO 2 and with 99% humidity, as described previously (54).…”
Section: Methodsmentioning
confidence: 99%